PERAN DINAS PERINDUSTRIAN KOPERASI DAN UKM KOTA MATARAM DALAM PEMBERDAYAAN PELAKU USAHA MIKRO KECIL MENENGAH - Andri Herijanto Effendi; Laili Hurriati; Ahmad Suhendri (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2023)
This study aims to determine the Empowerment of Small and Medium Enterprises (UKM) at the Office of Industry, Cooperatives and UMKM in Matarm City. The research method used is a qualitative type. Data collection techniques are interviews, observation and documentation. While the data analysis uses the inductive method. The results of this study indicate that empowerment (UKM) at the Office of Industry, Cooperatives and SMEs in Matarm City has not run optimally. Empowerment is carried out in 3 phases, namely: (1) the initial phase of the Mataram City Industry, Cooperative and MSME Office plays a full role in empowering UKM actors. (2) the participatory phase, the community and the government have collaborated in developing SMEs. (3) the emancipatory phase of the Mataram City Office of Industry, Cooperatives and SMEs, only plays a role as a supporter of every activity carried out by SMEs. However, the government is still constrained by the provision of facilities and infrastructure in the development of SMEs. Therefore, the empowerment of SMEs in the city of Mataram should provide adequate facilities and infrastructure, so that the implementation of training or counseling can run optimally and produce output that is in line with expectations.